VIABILITY FOR THE ESTABLISHMENT OF MUNICIPAL POLICE SERVICES (MPS) - DIKGARE, MATHUNYA KENNETH (My University, 2012)
The Constitution of the Republic of South Africa (108 of 1996) recognized the importance of Municipal Policing. As a result, the South African Police Services Act was amended to allow municipalities to establish their own Municipal Police Services (MPS). Apart from the traffic and by-law enforcement functions, the envisaged MPSs were also meant to perform the crime prevention function. However, only the metropolitan municipalities and one non-metropolitan municipality had shown interest in establishing their own MPSs. This study investigates the viability for establishing an MPS as well as how their functioning and effectiveness can be enhanced. It also investigates the possibility of replicating such an establishment in other municipalities. The study had adopted a qualitative methodology with interviews conducted with experts and practitioners in the field of security and policing. While the analysis of data had shown that the establishment of MPS can yield positive results in terms of localized policing, it had, unfortunately, revealed that the concept of municipal policing is seriously misunderstood. The majority still believes in the traditional form of policing, hence they view the MPS as a force multiplier for SAPS. By and large, the study has revealed the probability of profound results were the established and future MPSs to adopt a different approach from that of the national police. However, the findings have also painted a picture of serious policy flaws that may be seen as the reason why other municipalities are reluctant to establish their own MPSs. For this reason, a policy review was recommended with a view to addressing those areas that make municipal policing unviable.
MM thesis - P&DM
Keywords: Municipal policing; Police forces